The Role of Employee Performance During Covid-19: Do Motivation and Commitment Matter? - Indi Djastuti; Rr. Retno Sugiharti; Lela Lestari; Suharnomo Suharnomo (Jurnal Organisasi dan Manajemen, 2023)
Purpose – This study tries to analyze the relationship between job satisfaction and employee performance with the mediating variables of work motivation and organizational commitment in during the Covid-19 pandemic. Methodology – Structural Equation Model was built to capture the relationship between variables using purposive sampling, with the sample criteria being lecturers who have worked in both public and private tertiary institutions with a minimum work period of 2 years. When the questionnaire was distributed, the respondent was working through working-from-home scheme. In order to fulfil requirement from SEM model, 150 respondents were taken, and 128 questionnaire that can be used in estimation process. Findings – The results showed that work motivation and organizational commitment had no effect on employee performance, nor were they mediating variables on job satisfaction. This weak relationship proves that the pandemic is a difficult time for workers. Furthermore, satisfaction from a well-completed job is objectively beneficial, but the feeling appears confined to a task without high motivation and commitment. Originality – In case of pandemic time, Work motivation and Organizational commitment fail as a Mediating effect that connects job satisfaction to employee performance. Here’s proves that negative impact of the working-from-home policy is unavoidable.